Respiratory Interventions for Preterm Infants in LMICs: A Prospective Study From Cape Town, South Africa - Lategan, Ilse; Price, Caris; Rhoda, Natasha Raygaan; Zar, Heather J.; Tooke, Lloyd (Frontiers in Global Women's Health, 2022)
Background Preterm birth is a global public health issue and complications of preterm birth result in the death of approximately 1 million infants each year, 99% of which are in low-and-middle income countries (LMIC). Although respiratory interventions such as continuous positive airway pressure (CPAP) and surfactant have been shown to improve the outcomes of preterm infants with respiratory distress, they are not readily available in low-resourced areas. The aim of this study was to report the respiratory support needs and outcomes of preterm infants in a low-resourced setting, and to estimate the impact of a lack of access to these interventions on neonatal mortality. Methods We conducted a six-month prospective observational study on preterm infants <1,801 g admitted at Groote Schuur Hospital and Mowbray Maternity Hospital neonatal units in Cape Town, South Africa. We extrapolated results from the study to model the potential outcomes of these infants in the absence of these interventions. Results Five hundred and fifty-two infants (552) <1,801 g were admitted. Three hundred (54.3%) infants received CPAP, and this was the initial respiratory intervention for most cases of respiratory distress syndrome. Surfactant was given to 100 (18.1%) infants and a less invasive method was the most common method of administration. Invasive mechanical ventilation was offered to 105 (19%) infants, of which only 57 (54.2%) survived until discharge from hospital. The overall mortality of the cohort was 14.1% and the hypothetical removal of invasive mechanical ventilation, surfactant and CPAP would result in an additional 157 deaths and increase the overall mortality to 42.5%. A lack of CPAP availability would have the largest impact on mortality and result in the largest number of additional deaths (109). Conclusion This study highlights the effect that access to key respiratory interventions has on preterm outcomes in LMICs. CPAP has the largest impact on neonatal mortality and improving its coverage should be the primary goal for low-resourced areas to save newborn lives.